Elucidating the morphology and potential of purple datura (Datura metel) - Ranjan, Pragya; Ranjan, J K; Srivastava, Vartika (Indian Horticulture, 2025)
Purple-flowered datura (Datura metel L.), a member of the family Solanaceae, is renowned for its potent blend of toxicity and therapeutic value. In India, it is commonly known as dhattura and holds immense cultural and religious significance as a sacred offering to Lord Shiva. Unlike other datura species, D. metel is distinguished by its characteristic purple pigmentation on the stem. The plant produces spectacular purple or white flowers with strong ornamental potential, while its fruits and seeds possess narcotic, anodyne, and antispasmodic properties. This dual nature—both toxic and medicinal—highlights the delicate balance harnessed in traditional healing systems and underscores the scope for further exploration of its therapeutic applications. Moreover, its ability to thrive under harsh and contaminated environments presents promising opportunities for environmental remediation. The striking double- and triple-whorled cultivars, with their bright purple-white blossoms, also make D. metel highly suitable for aesthetic landscaping in uncultivated or degraded lands.